Biobanking-Budgets and the Role of Pathology Biobanks in Precision Medicine - Chris Andry MPhil, PhD; Elizabeth Duffy MA; Christopher A. Moskaluk MD, PhD; Shannon McCall MD; Michael H. A. Roehrl MD, PhD; Daniel Remick MD (Elsevier, 2017)
Biobanks have become an important component of the routine practice of pathology. At the 2016 meeting of the Association of Pathology Chairs, a series of presentations covered several important aspects of biobanking. An often overlooked aspect of biobanking is the fiscal considerations. A biobank budget must address the costs of consenting, procuring, processing, and preserving high-quality biospecimens. Multiple revenue streams will frequently be necessary to create a sustainable biobank; partnering with other key stakeholders has been shown to be successful at academic institutions which may serve as a model. Biobanking needs to be a deeply science-driven and innovating process so that specimens help transform patient-centered clinical and basic research (ie, fulfill the promise of precision medicine). Pathology's role must be at the center of the biobanking process. This ensures that optimal research samples are collected while guaranteeing that clinical diagnostics are never impaired. Biobanks will continue to grow as important components in the mission of pathology, especially in the era of precision medicine.